2016
DOI: 10.1111/nyas.13035
|View full text |Cite
|
Sign up to set email alerts
|

Neuroscience of aesthetics

Abstract: Aesthetic evaluations are appraisals that influence choices in important domains of human activity, including mate selection, consumer behavior, art appreciation, and possibly even moral judgment. The nascent field of neuroaesthetics is advancing our understanding of the role of aesthetic evaluations by examining their biological bases. Here, we conduct a selective review of the literature on neuroaesthetics to demonstrate that aesthetic experiences likely emerge from the interaction between emotion-valuation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
191
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 221 publications
(200 citation statements)
references
References 169 publications
(277 reference statements)
7
191
1
1
Order By: Relevance
“…In line with this idea, the unique ability of humans to appreciate aesthetic rewards such as music relies on higher order perceptual/ cognitive analysis and encompasses learning, experience, and cultural factors that would be expected to involve cortical systems (26)(27)(28). Our results also support the notion that to derive pleasure from music, the cortical and subcortical systems must act in concert; in particular, we found the interplay between the right STG and VS to be crucial.…”
Section: Discussionsupporting
confidence: 78%
“…In line with this idea, the unique ability of humans to appreciate aesthetic rewards such as music relies on higher order perceptual/ cognitive analysis and encompasses learning, experience, and cultural factors that would be expected to involve cortical systems (26)(27)(28). Our results also support the notion that to derive pleasure from music, the cortical and subcortical systems must act in concert; in particular, we found the interplay between the right STG and VS to be crucial.…”
Section: Discussionsupporting
confidence: 78%
“…Without such a framework, individual studies remain isolated findings untethered to programmatic advances in understanding. Neuroaesthetics was helped by the introduction of general psychological and neuroscientific models that have since been debated and refined (Chatterjee & Vartanian, 2016;Tinio, 2013;Nadal, Munar, Capó, Rosselló, & Cela-Conde, 2008;Jacobsen, 2006;Chatterjee, 2004a;Leder et al, 2004). Here, we apply one such general framework, the aesthetic triad, to architecture.…”
Section: Double Framingmentioning
confidence: 99%
“…In this study, we apply lessons from recent developments in neuroaesthetics, a discipline that investigates the neurobiological underpinnings of aesthetic experiences of beauty and art (Chatterjee & Vartanian, 2016), to the neuroscience of architecture. These ideas and methods can be used to study aesthetic experiences in the built environment (Eberhard, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the mPFC is a core region of the social brain (Amodio and Frith, 2006; Van Overwalle, 2009): neuroimaging evidence suggests that it is involved in several aspects of social cognition, mediating self-representation (e.g., Gusnard et al , 2001; D'Argembeau et al , 2007; Jenkins and Mitchell, 2011), first impression formation (e.g., Mitchell et al , 2005a; Baron et al , 2011), personality trait inference (e.g., Ma et al , 2011, 2013a), attribution of mental states (Mitchell et al , 2005b), and social categorization, including stereotyping (Knutson et al , 2007; Quadflieg et al , 2009; Gilbert et al , 2012). Studies in the aesthetic domain found also consistent activation in the mPFC in response to preferred stimuli, whether faces or artworks (Jacobsen et al , 2006; Chatterjee et al , 2009; Chatterjee and Vartanian, 2016). Lesion studies confirm the central role of the mPFC in social cognition.…”
Section: Introductionmentioning
confidence: 84%